Lessons learned in the implementation of supplementary immunization activity (SIA) field guidelines for injectable vaccines – Experiences from Tanzania. Issue 49 (17th November 2020) - Mohamed, Nassor; Simba, Daudi; Mphuru, Alex; Lyimo, Dafrossa; Kyesi, Furaha
Abstract: Background: To achieve Measles and Rubella elimination and Polio Endgame goals, Tanzania implemented country-wide integrated Supplementary Immunization Activities (SIAs) in October 2019 involving two injectable vaccines of MR and IPV. The SIAs targeted children aged between 9 and 59 months for Measles-Rubella and 18 to 42 months for IPV vaccines. This article aims to share lessons learnt in the implementation of SIAs field guidelines in Tanzania in 2019 to inform future implementation of the SIAs within and outside the country's boundaries. Methods: Focus groups discussions (FGDs) were conducted among Regional Immunization and Vaccines Officers from all regions and National Supervisors and Partners responsible for implementing the SIAs. Key areas discussed were pre-planning activities, implementation, monitoring and evaluation of the SIAs based on key thematic areas including; planning and coordination, logistics management, trainings, and demand creation. Pre-described templates were used to guide the discussion and keep record of the discussions. Results: The SIAs achieved national target based on administrative coverage. This was due to a high sense of ownership of the SIAs and strong staff commitment to attain high coverage rates manifested through effective planning and coordination within and between levels; effective execution of SIAs activities; involvement of key stakeholders at all levels; and strong advocacy, communication and social mobilization activities. Despite the success observed through administrative coverage, the WHO target of attaining 95% coverage using the gold standard - national coverage survey, was not reached. The main barrier to success was inadequate and delayed disbursement of funding. Conclusion: The 2019 SIA achieved high administrative coverage as a result of effective coordination; adequate micro-planning; timely logistical preparations; and effective demand creation activities. Future campaigns need to give high priority to hard-to-reach and densely populated areas during planning and ensure timely disbursement of funds to the operational level during implementation.